ASSESSMENT OF FISCAL POLICY IN LATVIA - Zubule, Erika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The aim of the research is: to evaluate the fiscal policy in Latvia in accordance with the theoretical and practical conclusions of scientific investigations in the world, to determine the main fiscal risks and to find fiscal policy gaps in national government budgeting as well as in the use of funds and to define recommendations for making a sustainable fiscal policy in the country. At present, economic development in the world and Europe, the geopolitical situation, the migration of the population as well as the domestic problems of the development of Latvia pose new challenges to the government’s fiscal policy; they create new fiscal risks and problems that require strong fiscal discipline and an efficient fiscal policy. The fact that Latvia did not have fiscal reserve resources for easier survival of the crisis is a severe and painful lesson about the errors in the fiscal policy. New circumstances that have occurred recently have to be taken into account by the policy makers. In order to build an effective fiscal policy, the following has to be found out: the most important factors of impact, whether they are of objective or subjective nature, and what fiscal risks may threaten the performance of individual fiscal indicators, and how big must be the fiscal security reserve.